A test of aphasia in malayalam - Jeny Elizabeth Philip (Journal of All India Institute of Speech and Hearing)
As there is no aphasia test in Malayalam to test the communication skills in aphasics, an attempt was made to construct a test based on WAB (Kertesz, 1979). The new test thus developed for aphasics in Malayalam consists of 4 language subtests. (1) Spontaneous speech : Information content, Fluency. (2) Auditory comprehension (3) Repetition (4) Naming and 3 performance tests (5) Reading (6) Writing (7) Praxis, and a subtest to measure intelligence and visuospatial performance. (8) Construction: Drawing